2021
DOI: 10.20473/bhsj.v4i2.28875
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Burden And Psychosocial Factors In Mothers With Autism Spectrum Disorder Children

Abstract: Introduction: Burden experienced by mother can delayed the success of therapy to ASD children. This study aims to determine the correlation of psychosocial factors and caregiver burden in mothers with ASD children.Methods: This study was a cross-sectional analytic study on mothers with ASD children at the Children's Daycare Dr.Soetomo General Hospital. The research instrument used sociodemographic questionnaire and a Caregiver Burden Assessment (CBA). Results: This study was followed by 26 mothers with ASD chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
1
0
0
Order By: Relevance
“…Autistic children also need to attend additional regular therapy sessions and rehabilitation programs; thus, caregivers need to spend more time on this rather than having their leisure time. The results of this study are consistent with previous research by Fithriyah and Carrasco (2021), which reported that undergoing treatments requires more time, patience, and effort than necessary, which results in anxiety, depression, and psychological anguish.…”
Section: The Association Between Parental Stress and Their Sociodemog...supporting
confidence: 92%
“…Autistic children also need to attend additional regular therapy sessions and rehabilitation programs; thus, caregivers need to spend more time on this rather than having their leisure time. The results of this study are consistent with previous research by Fithriyah and Carrasco (2021), which reported that undergoing treatments requires more time, patience, and effort than necessary, which results in anxiety, depression, and psychological anguish.…”
Section: The Association Between Parental Stress and Their Sociodemog...supporting
confidence: 92%
“…Hal tersebut dikarenakan kecemasan yang dialami ibu dengan anak ASD berhubungan dengan gejala dan masalah perilaku yang dimiliki anak (Hutasoit et al, 2023). Selain itu, ibu dengan anak ASD juga mengalami stres dan beban pengasuhan dikarenakan beberapa faktor seperti kurangnya pengatahuan tentang ASD, ekonomi, dan kelelahan fisik yang akan mengakibatkan kualitas hidup yang menurun (Fithriyah et al, 2020).…”
unclassified